Some applications of quadrature rules for mappings on \(L_p[u,v]\) space via Ostrowski-type inequality - Irshad, Nazia; Khan, Asif R. (J. Numer. Anal. Approx. Theory, 2017)
Some Ostrowski-type inequalities are stated for \(L_p[u,v]\) spaces and for mappings of bounded variations. Applications are also given for obtaining error bounds of some composite quadrature formulae.